Soil and Sand Contamination with Canine Intestinal Parasite Eggs as a Risk Factor for Human Health in Public Parks in Niš (Serbia) - Ristić, M. (Helminthologia, 2020)
Regarding geographical distribution and clinical relevance, the most common canine geohelminths are Toxocara canis, ancylostomatids, and Trichuris vulpis. Canine intestinal parasites from the soil and sand present an important potential serious human health hazard, especially for the children preschool and school – age. This paper aimed to establish the degree of contamination of soil and sand with zoonotic parasites from the canine feces and the degree of risk they could pose for human health in public places and playgrounds in the city of Niš. Our parasitological study involved 200 soil samples and 50 sand samples from the public parks in the city of Niš in southeastern Serbia (43°19′15″N, 21°53′45″ E). From several locations, about 100 g of soil and sand was collected based on the bioclimatic indices. Parasitological diagnosis was performed using conventional qualitative and quantitative coprological methods, abiding by the recommendations about the diagnosis of parasitic diseases. In 38 – 46 % of soil samples and 40 % of sand samples seven species of endoparasites were diagnosed. In the samples of soil, a medium and high degree of contamination with the ascarid T. canis (14 – 22 %) was detected, as well as a low and medium degree of contamination with ancylostomatids (4 – 12 %), and in the samples of sand, a variable degree of contamination with the helminths T. canis (26 %) and A. alata (16 %) was found. A statistically significant difference was found in the contamination with A. alata eggs between the samples of sand and samples of soil. The studied public surfaces represent the reservoir of zoonotic parasites, which is a public health problem requiring a synergistic action of several factors to be successfully resolved, i.e. the implementation of prevention, surveillance, and control measures.